Sosialisasi dan Pelatihan (Workshop) Bedah Ruang Kantor RW 07 – RW 12 Kelurahan Kebon Pala Jakarta Timur - Bambang Erwin; Sri Pare Eni; Ulinata Ulinata; Grace Putri Dianty; Luky Wirawan; Imelda - (JURNAL ComunitÃ Servizio : Jurnal Terkait Kegiatan Pengabdian kepada Masyarakat, terkhusus bidang Teknologi, Kewirausahaan dan Sosial Kemasyarakatan, 2023)
Architecture Study Program at Universitas Kristen Indonesia collaborated with Dekoruma and Postgraduate Program for Community Service Activities entitled Green Action 29 entitled Socialization and Training (Workshop) for Office Space Surgery RW 07 – RW 12 in Kebon Pala Village, East Jakarta City. This activity is also a continuation of the Community Service Activities that have been carried out in RW 01- RW 06 which also has the same goal, namely to provide insight and knowledge related to renovating office space, especially the RW office in the Kebon Pala Village which was conveyed by the resource persons. The method is to coordinate with the Village Head and his staff, making preparations until this activity is carried out. As a result, material related to office room renovations was well conveyed by the resource person and to increase the enthusiasm of the participants, a competition would be held so that it could also be known to what extent the participants understood the material presented. Keywords: Socialization, Kebon Pala, Make Over